2010
DOI: 10.3354/meps08652
|View full text |Cite
|
Sign up to set email alerts
|

Bowhead whale Balaena mysticetus seasonal selection of sea ice

Abstract: Highly mobile large-bodied organisms are adapted to seasonal variation associated with polar environments. We used satellite tracking data from 27 bowhead whales Balaena mysticetus of the Eastern Canada-West Greenland population to test for movement and habitat selection of the highly variable sea ice landscape that encompasses near-complete coverage in winter to nearcomplete absence in summer. We demarcated 2 bowhead whale seasons based on movement behaviour identified from inflection points of polynomial reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 67 publications
3
73
2
Order By: Relevance
“…Previous studies on movements of the Eastern Canada -West Greenland bowhead whale population show that these animals are widely distributed throughout the eastern Canadian Arctic and West Greenland, where they perform long seasonal migrations (Heide-Jørgensen et al, 2003b). They overwinter in Hudson Strait, Cumberland Sound, West Greenland, and the North Water polynya (Ferguson et al, 2010). In spring, they inhabit the west coast of Greenland (particularly Disko Bay, Tervo et al, 2009), Cumberland Sound, Foxe Basin, and Lancaster Sound in Canada (Ferguson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on movements of the Eastern Canada -West Greenland bowhead whale population show that these animals are widely distributed throughout the eastern Canadian Arctic and West Greenland, where they perform long seasonal migrations (Heide-Jørgensen et al, 2003b). They overwinter in Hudson Strait, Cumberland Sound, West Greenland, and the North Water polynya (Ferguson et al, 2010). In spring, they inhabit the west coast of Greenland (particularly Disko Bay, Tervo et al, 2009), Cumberland Sound, Foxe Basin, and Lancaster Sound in Canada (Ferguson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Based on resource selection functions to evaluate seasonal selection of ice (coverage, thickness, and floe size), Ferguson et al (2010b) showed that sea ice was a major factor influencing bowhead whale seasonal distribution. Bowhead whales were found to select relatively low ice coverage, thin ice, and small floe areas in winter close to the maximum ice extent as opposed to summer when whales selected high ice coverage, thick ice, and large floe size areas.…”
Section: Climate Change and The Diet Of Bowhead Whalesmentioning
confidence: 99%
“…These samples originated from an area south of 59°N, over 1,000 km south of the current Arctic range of the bowhead whale [11][12][13][14][15][16][17][18][19][20][21][22] . We successfully genetically identified the species of 27 ancient samples, of which 15 were bowhead whales ( Supplementary Fig.…”
Section: Species Occurrencementioning
confidence: 99%
“…The bowhead whale is a true Arctic species that remains in polar waters throughout the year 12 . Like the polar bear, it is a sentinel species of the Arctic marine ecosystem due to its dependence on the sea ice 13,14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation